Immunological persistence in 4-6 and 7-9 year olds previously vaccinated in infancy with hexavalent DTPa-HBV-IPV/Hib - Zinke, Michael; Disselhoff, Johann; Gartner, Britta; Marie Jacquet, Jeanne (Human vaccines, 2010)
Background: The combined diphtheria-tetanus-pertussis-hepatitis B-inactivated poliomyelitis-Haemophilus influenzae conjugate vaccine (DTPa-HBV-IPV/Hib, Infanrix HexaTM GlaxoSmithKline Biologicals, Rixensart, Belgium) is the only hexavalent vaccine currently licensed for primary and booster vaccination of infants and provides simultaneous protection against six major diseases of childhood. The persistence of the immune response in children aged 4-6 and 7-9 years of age previously vaccinated with four doses of DTPa-HBV-IPV/Hib vaccine was assessed (www.clinical trials.gov.au 106744 NCT00356564 and 106745 NCT00335881). Methods: A blood sample was collected from 403 children, all of whom had received 3-dose primary vaccination and a booster dose in the second year of life with DTPa-HBV-IPV/Hib, in previous clinical vaccine trials in Germany. Results: Mean time from the fourth DTPa-HBV-IPV/Hib dose until serological follow-up ranged between 3.6 and 6.4 years. After the 4th DTPa-HBV-IPV/Hib dose, in subjects who had not received additional booster doses, seroprotective antibody levels persisted up to 9 years of age in ≥90% of subjects for diphtheria, Hib, and poliomyelitis, in 77.2% subjects for Hepatitis B and in 64.7% of subjects for tetanus. Anti-pertussis toxin antibodies remained detectable in no more than 38.2% of subjects. Conclusion: With the exception of PT, the combined DTPa-HBV-IPV/Hib induces long lasting immune response against all vaccine antigens. Falling seropositivity against PT over time supports the recommended administration of a pertussis booster dose in 5-6 year old children in Germany.